Mouse oncostatin M: an immediate early gene induced by multiple cytokines through the JAK-STAT5 pathway. - Yoshimura, A (1996)
Oncostatin M (OSM) is a member of the interleukin-6 (IL6)-related cytokine subfamily that includes IL6, IL11, leukemia inhibitory factor (LIF), ciliary neurotrophic factor and cardiotrophin-1. While human OSM has been characterized and the bovine OSM gene was recently cloned, the murine counterpart had not been identified. Here we describe molecular cloning of murine OSM as an immediate early gene induced by a subset of cytokines including IL2, IL3 and erythropoietin (EPO) in myeloid and lymphoid cell lines. The induction kinetics of OSM are rapid and transient, reaching a maximal level within 30-60 min and decreasing thereafter. Induction of OSM depends on the signals generated by the membrane-proximal region of the EPO receptor as well as that of the beta chain of the IL3/GM-CSF receptor, which activate JAK2 and STAT5. About 100 bases upstream of the transcription initiation site of the OSM gene contains a possible STAT5 binding site which is essential for IL2, IL3 and EPO-dependent promoter activity of the OSM gene. Expression of STAT5 and the EPO receptor in COS cells conferred EPO-dependent activation of the OSM promoter. Moreover, the mutant IL2 receptor lacking the ability to activate STAT5 induced c-myc but failed to induce OSM. Thus OSM is one of the common targets of a subset of cytokines that activate STAT5. The murine OSM gene is located near to the LIF gene, expressed at high levels in bone marrow and possesses similar biological activity to human OSM. Identification of murine OSM as a cytokine-inducible immediate early gene provides a new insight into the physiological function of this unique cytokine.